Help-seeking behaviors among college students who have experienced intimate partner violence and childhood adversity - Seon, Jisuk (Journal of family violence, 2022)
Purpose This study examines the relationships among adverse childhood experiences (ACEs), intimate partner violence (IPV) victimization, and two types of adulthood help-seeking behaviors in adulthood—formal and informal. The effects of IPV on formal and informal help-seeking, and the effects of ACEs on IPV and formal and informal help-seeking were assessed. Method: The analytic sample of this study is 591 college students from seven universities in the U.S. and Canada who reported at least one type of ACE and IPV victimization. Results: Results from structural equation modeling show that ACEs were positively associated with IPV victimization. IPV victimization was positively associated with formal and informal help-seeking. ACEs were positively associated with formal but not informal help-seeking. Conclusions: These findings suggest that ACEs influence not only violent experiences in adulthood but also behaviors in relation to seeking help following victimization in adulthood.